1991
DOI: 10.3349/ymj.1991.32.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella entericasubspeciesdiarizonaebacteremia in an infant with enteritis: a case report

Abstract: The septicemia caused by the Arizona group organism is rare and usually observed in adults with underlying diseases. In Korea, Salmonella infection is common, but a report of Arizona infection is unknown. We isolated S. entercia subsp. diarizonae from blood of a 6-month-old infant. The serovar was determined as 28:z10:-, a rare one in America. The isolate was susceptible to ampicillin, chloramphenicol, cotrimoxazole and others. The patient rapidly recovered with ampicillin and gentamicin therapy. Clinical labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…was 7.33 %, this rate was fully compared to previous studies done in Burkina Faso (2%) and in southeastern and eastern Korea reported by Chong et al (1991) and in Africa reported by Bonkoungou (2013).…”
Section: Resultssupporting
confidence: 59%
“…was 7.33 %, this rate was fully compared to previous studies done in Burkina Faso (2%) and in southeastern and eastern Korea reported by Chong et al (1991) and in Africa reported by Bonkoungou (2013).…”
Section: Resultssupporting
confidence: 59%
“…This study demonstrated that the prevalence of Salmonella in free-living snakes in Japan reached 58.6z and S. enterica subspecies I, which comprise the majority of pathogenic Salmonella serotypes of humans and other animals, was present in 12.6z, while S. enterica subspecies IIIb, which is not highly pathogenic to humans but causes sporadic disease, particularly in infants (13), was widely distributed and present in 41.1z of the studied snakes. In contrast, the prevalence of S. enterica subspecies IIIa and IV was low.…”
Section: Discussionmentioning
confidence: 73%
“…arizonae (IIIa) and diarizonae (IIIb) can be challenging with routine biochemical and serological tests. Some members of these subspecies differ from other Salmonella by their ability to ferment lactose (Lapage & Jayaraman, 1964;Chong et al, 1991;Davies et al, 2001). As lactose fermentation is one of the key diagnostic principles on which standard methods for the isolation of Salmonella are based, lactose-positive Salmonella strains represent a special diagnostic problem and may go unnoticed.…”
Section: Discussionmentioning
confidence: 99%